2015
DOI: 10.1111/jar.12163
|View full text |Cite
|
Sign up to set email alerts
|

Cybervictimization of Young People With an Intellectual or Developmental Disability: Risks Specific to Sexual Solicitation

Abstract: Background Studies demonstrate that youth are vulnerable to online sexual solicitation. However, no study has estimated this risk for youth diagnosed with an intellectual or developmental disability (IDD). Methods A literature review of the risk factors associated with online sexual solicitation in youths was done using electronic databases, such as PsychInFO, ERIC, MEDLINE and Scopus. Results Fifty‐seven published papers were found relevant. However, only two pertained to the population with IDD. Sexual and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 65 publications
(194 reference statements)
6
55
0
9
Order By: Relevance
“…loneliness, depression, social isolation) are more prevalent in youth with IDD than the general population. One rare study on this topic is that reported by Didden et al (2009), the results of which contradict to some extent the conclusions of Normand et al (2016). Didden et al (2009) conducted a questionnaire survey of the prevalence of Internet and mobile phone cyber-bullying amongst a group of young people with IDD aged between 12 and 19.…”
Section: Perceptions Of Internet Riskmentioning
confidence: 79%
“…loneliness, depression, social isolation) are more prevalent in youth with IDD than the general population. One rare study on this topic is that reported by Didden et al (2009), the results of which contradict to some extent the conclusions of Normand et al (2016). Didden et al (2009) conducted a questionnaire survey of the prevalence of Internet and mobile phone cyber-bullying amongst a group of young people with IDD aged between 12 and 19.…”
Section: Perceptions Of Internet Riskmentioning
confidence: 79%
“…However, online browsing or communication that requires a great deal of reading or writing poses problems (Harrysson, Svensk, & Johansson, 2004;McClimens & Gordon, 2009;Molin et al, 2015;Shpigelman & Gill, 2014;Wong, Chan, Li-Tsang, & Lam, 2009). And although, compared with the rest of the population, fewer of these people use the Internet and spend less time on it (Parsons, Daniels, Porter, & Robertson, 2008;Wells & Mitchell, 2014), they seem to be more at risk of online sexual victimization or extortion Normand & Sallafranque St-Louis, 2015Wells & Mitchell, 2014). Consequently, it is not unusual for the people around them to attempt to control or limit their access to the Internet (Chadwick et al, 2013;Löfgren-Mårtenson et al, 2015).…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…People who do not understand these rules could expose themselves to new forms of victimization or exclusion, such as sexual solicitation online, identity theft, impulse buying, harassment, and exposure to unwanted content (Government of Canada, 2015;Holtfreter, Reisig, Pratt, & Holtfreter, 2015). They may even go as far as jeopardizing their health and safety, for example, by accepting to meet and have unsafe sex with strangers found on the Web (Normand & Sallafranque St-Louis, 2015;.…”
Section: Technical Dimensionmentioning
confidence: 99%
“…She believes that the greatest danger perceived by people with ID is to be isolated and deprived of romantic relationships. Normand and Sallafranque St-Louis (2015) identified the variables associated with sexual cyber-solicitation of youth published in the scientific literature. Their review shows that past or present sexual or physical abuse, social isolation, loneliness, depression and chatting increased the likelihood of falling prey to sexual cybersolicitation.…”
Section: Risks Associated With Online Communicationmentioning
confidence: 99%
“…Facebook, Second Life), enable people to broaden their network of friends, receive support, forge positive identities, and participate fully in their real and virtual communities (Amichai-Hamburger, 2013;García-Galera, Del-Hoyo-Hurtado, & Fernández, 2014;Moisey & van de Keere, 2007;Raghavendra, Newman, Grace, & Wood, 2013;Subrahmanyam, Greenfield, & Brendesha, 2004;Ybarra, Mitchell, Palmer, & Reisner, 2014). However, very little is known about Internet use by people with ASD or ID especially (Caton & Chapman, 2016;Hoppestad, 2013;Lussier-Desrochers, Dupont, Lachapelle, & Leblanc, 2011;Normand & Sallafranque St-Louis, 2015;Sallafranque St-Louis & Normand, 2011). Caton and Chapman's (2016) recent review on the use of social media shows not only that research in this area is sparse, but also that research methodologies are weak.…”
Section: Introductionmentioning
confidence: 99%